ANALYSIS OF THE IMPACT OF PJBL AND DIGITAL PUZZLE INTEGRATION: A SYSTEMATIC REVIEW OF ELEMENTARY STUDENTS’ WRITING SKILLS - Jian Alfian; Sri Dewi Nirmala; Nidya Chandra Muji Utami (Universitas Majalengka, 2026)
The persistently low narrative writing skills among elementary students are mainly caused by conventional teaching methods and the limited use of interactive media that stimulate imagination and sequential thinking. This study aims to analyze the impact of integrating Project-Based Learning (PjBL) and digital serial picture puzzles on improving students’ narrative writing skills through a Systematic Literature Review (SLR) approach. The SLR was conducted by systematically identifying, screening, evaluating, and thematically synthesizing 18 relevant articles published between 2018 and 2025, sourced from national and international databases. Data analysis involved thematic synthesis, comparative mapping, and content analysis to capture the effectiveness and synergy of the two approaches. The synthesis results indicate that digital serial picture puzzles are effective in enhancing students’ abilities to organize storylines, describe characters, and understand narrative structures logically and creatively. The application of PjBL significantly improves students’ motivation, creativity, independence, and collaboration in the writing process. The integration of PjBL and digital puzzles produces a synergistic effect, resulting in higher quality narrative writing in terms of coherence, organization, and content depth. However, the review also found a lack of direct implementation studies on the integration of these two approaches. The study recommends the development of an integrated PjBL–digital puzzle learning model and teacher training to support optimal implementation in elementary schools.